BIOHACKING & TRANSHUMANISM, MAPPING EMERGING DISCOURSES: A BIBLIOMETRIC REVIEW - Felipe Guevara-Pezoa (Instituto Politécnico de Viseu, 2024)
Introduction: Biohacking's emergence has reshaped scientific research, especially within transhumanism and biological manipulation. Evaluating its impact on the scientific community is crucial for defining future research directions and communication in this field. Objective: To critically examine perspectives, approaches, and debates in academic literature to develop a comprehensive understanding of the ethical, social, and cultural implications of technological advancement within the transhumanist context. Methods: SCOPUS and bibliometric analysis were employed to quantify biohacking's influence. Social Network Analysis identified key themes and research focus areas. Results: North American and European countries led in scientific productivity. Published articles and citation impact showed a moderate to low index. Social Network Analysis highlighted ethical considerations, social implications, and an emerging discourse on cognitive evolution. Conclusion: The results highlight the need for comprehensive education and communication strategies to ensure that the public is well-informed about the risks, benefits, and ethical considerations associated with genetic modification technologies. Therefore, more research on legislation and regulations is required.